Colchicine treatment can be discontinued in a selected group of pediatric FMF patients - Keren Cohen; Shiri Spielman; Rotem Semo-Oz; Guy Bitansky; Maya Gerstein; Yonatan Yacobi; Asaf Vivante; Irit Tirosh (BMC, 2023)
Abstract Objectives Familial Mediterranean Fever (FMF) patients are required to adhere to a life-long treatment with colchicine, primarily for preventing amyloidosis. As some patients may be asymptomatic for long periods of time, it remains unclear whether it is possible to discontinue colchicine treatment in a selective group of patients. We aimed to identify predictive characteristics for a successful cessation of colchicine therapy. Methods Out of 646 FMF pediatric patients followed in our referral FMF clinic, colchicine treatment was discontinued in 51 patients. In this study we compared the genetic, demographic, and clinical characteristics between patients for whom a successful cessation of therapy was made (Group 1; n = 21) and patients for whom cessation of therapy was deemed a failure (Group 2; n = 30) and consequently had to resume colchicine therapy. Results Patients for whom a successful cessation of therapy was achieved had no biallelic pathogenic MEFV mutations, were less likely to have "severe attacks" (two or more FMF characteristic symptoms) (24% vs 80%; P = 0.000067) and did not require higher than 1 mg/day of colchicine, prior to the drug cessation. Remission duration under colchicine treatment was significantly higher in group 1 compared with group 2 (4.36 years ±2.12 vs 2.53 years ±2; P = 0.0036). Conclusion This study supports the concept of colchicine free remission in a minority of FMF patients (3%). Holding treatment, under close monitoring, may be reasonable when selecting the appropriate patients.